2021
DOI: 10.3390/su14010292
|View full text |Cite
|
Sign up to set email alerts
|

Cause-Related Marketing and Ethnocentrism: The Moderating Effects of Geographic Scope and Perceived Economic Threat

Abstract: Amongst the various factors that managers need to consider when designing a CRM campaign is the cause’s geographic scope, i.e., should the CRM campaign benefit local, national, or international communities? Although previous research has examined the importance of geographic scope in the effectiveness of the CRM campaigns, it has largely ignored consumer reactions to CRM campaigns from a local cultural identity perspective, such as ethnocentric identity. This study brings together these two important factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 85 publications
(192 reference statements)
0
12
0
Order By: Relevance
“…The rationale behind cause-related marketing is to create a mutually beneficial relationship between a company and a social cause (Grau and Folse, 2007). It allows companies to align themselves with a cause that resonates with their target consumers, thereby increasing their sales (Boulouta and Manika, 2021), enhanced brand image (Homssi et al, 2023;Singh et al, 2020), reputation (Chaabouni et al, 2021;Pandey and Bajpai, 2022) and stronger consumer brand identification (Boulouta and Manika, 2021). By associating with a social cause, they stand out from rivals and attract socially concerned customers who prioritize supporting brands that contribute to social causes (Homssi et al, 2023).…”
Section: Effect Of Carm On the Customers' Pi 1121mentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale behind cause-related marketing is to create a mutually beneficial relationship between a company and a social cause (Grau and Folse, 2007). It allows companies to align themselves with a cause that resonates with their target consumers, thereby increasing their sales (Boulouta and Manika, 2021), enhanced brand image (Homssi et al, 2023;Singh et al, 2020), reputation (Chaabouni et al, 2021;Pandey and Bajpai, 2022) and stronger consumer brand identification (Boulouta and Manika, 2021). By associating with a social cause, they stand out from rivals and attract socially concerned customers who prioritize supporting brands that contribute to social causes (Homssi et al, 2023).…”
Section: Effect Of Carm On the Customers' Pi 1121mentioning
confidence: 99%
“…Cause proximity also affects customers' CaRM responses (Grau and Folse, 2007). Cause proximity is defined as a CaRM campaign's geographic location and customer proximity (Boulouta and Manika, 2021). According to the existing literature (Grau and Folse, 2007;Vanhamme et al, 2012), customers' positive impressions of CaRM activities are affected by the proximity of a cause.…”
Section: Cause-related Marketing (Carm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The cause-and-effect scheme is also evident in fields such as sustainable solid waste management [21]. Marketing is one of the business fields that heavily relies on cause-and-effect analysis [22][23][24]. The goal here is to demonstrate the widespread applicability of cause and effect across disciplines.…”
Section: The Analysis Phasementioning
confidence: 99%
“…According to Siamagka & Balabanis (2015), consumer ethnocentrism during crisis serves as a self-defence reflex of domestic economy, organizations and individuals against foreign competition and imports. Consequently, it can be concluded that there was an increase in ethnocentric tendencies during the current COVID 19 virus pandemic (Boulouta & Manika, 2022).…”
Section: Introductionmentioning
confidence: 98%